HARMONISASI UNDANG-UNDANG DASAR 1945 DENGAN KETENTUAN INTERNASIONAL TENTANG MASYARAKAT EKONOMI ASEAN 2015 (Asean Economic Community/AEC 2015) - Aini, Desy Churul (FIAT JUSTISIA, 2015)
One form of regional cooperation is followed by Indonesia with his participation as a member of ASEAN (Association of South East Asian Nations) which was established on the basis of the Bangkok Declaration, on 8 August 1967. By the 21st century, ASEAN agreed to develop an integrated regional by forming a community of nations in Southeast Asia open, peaceful, stable and prosperous, mutual care, tied together in a dynamic partnership in 2020. Expectations are outlined in the ASEAN vision 2020 in Kuala Lumpur in 1997. To realize these expectations ratify ASEAN Bali Concord II at the 9th ASEAN Summit in Bali in 2003 which approved the establishment of an ASEAN Community (ASEAN Community) and the target is accelerated into 2015. The result shows there is disharmony between 1945 to the international provisions of the AEC 2015 in which the rules on economic issues and social welfare in 1945 are listed in Chapter XIV National Economy and social welfare, Article 33 (1), (2), (3) and (4), while based on the AEC 2015 blueprint contains four pillar framework or MEA. Disharmony both conditions contained in 4 (four) things into focus, namely the harmonization of aspects of the legal principle, an agreement on the authority, goal setting and alignment settings on the environment and surrounding communities.Keywords: Disharmony, the Constitution 1945, Asean Economic Community